Akt1 signalling supports acinar proliferation and limits acinar‐to‐ductal metaplasia formation upon induction of acute pancreatitis. Issue 1 (22nd November 2019) - Chen, Rong; Malagola, Ermanno; Dietrich, Maren; Zuellig, Richard; Tschopp, Oliver; Bombardo, Marta; Saponara, Enrica; Reding, Theresia; Myers, Stephen; Hills, Andrew P; Graf, Rolf; Sonda, Sabrina
Abstract: Molecular signalling mediated by the phosphatidylinositol‐3‐kinase (PI3K)–Akt axis is a key regulator of cellular functions. Importantly, alteration of the PI3K–Akt signalling underlies the development of different human diseases, thus prompting the investigation of the pathway as a molecular target for pharmacologic intervention. In this regard, recent studies showed that small molecule inhibitors of PI3K, the upstream regulator of the pathway, reduced the development of inflammation during acute pancreatitis, a highly debilitating and potentially lethal disease. Here we investigated whether a specific reduction of Akt activity, by using either pharmacologic Akt inhibition, or genetic inactivation of the Akt1 isoform selectively in pancreatic acinar cells, is effective in ameliorating the onset and progression of the disease. We discovered that systemic reduction of Akt activity did not protect the pancreas from initial damage and only transiently delayed leukocyte recruitment. However, reduction of Akt activity decreased acinar proliferation and exacerbated acinar‐to‐ductal metaplasia (ADM) formation, two critical events in the progression of pancreatitis. These phenotypes were recapitulated upon conditional inactivation of Akt1 in acinar cells, which resulted in reduced expression of 4E‐BP1, a multifunctional protein of key importance in cell proliferation and metaplasia formation. Collectively, our results highlight the critical role played by Akt1 during the development of acute pancreatitis in the control of acinar cell proliferation and ADM formation. In addition, these results harbour important translational implications as they raise the concern that inhibitors of PI3K‐Akt signalling pathways may negatively affect the regeneration of the pancreas. Finally, this work provides the basis for further investigating the potential of Akt1 activators to boost pancreatic regeneration following inflammatory insults. © 2019 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.